Intracorneal Inlays for the Correction of Presbyopia. Issue 5 (September 2017) - Binder, Perry S.
Abstract : Abstract: The current nonsurgical approaches for the correction of presbyopia are spectacles or contact lenses or the use of pharmaceuticals to create an artificial pupil and/or to stimulate residual accommodation. Refractive surgical procedures use a monovision approach and/or a multifocal corneal laser ablation with or without the induction of negative spherical aberration to improve near vision. More recently, new surgical approaches include intracorneal inlays. Inlay approaches include increasing corneal curvature alone, implanting a multifocal inlay, or by implanting a small aperture device that functions as a pinhole to restore unaided near and intermediate visual acuity. This review presents an analysis of the history and development of the various inlay approaches designed to improve presbyopia. Unlike other refractive surgical approaches, these newer techniques are removable. Each has its advantages and disadvantages.